Desain Interaksi Mesin Pencatat untuk Tunanetra Menggunakan Raspberry Pi - Nashir Umam Hasbi; Hurriyatul Fitriyah; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Recording is a basic requirement for every learner, not except for visually impaired students who have the need to record information received. However, visually impaired people have difficulties to use the commonly used recording media, it needs a special tool or application to help the visually impaired in taking notes. Therefore, in this research will be made a recording machine that can be used by the visually impaired with layout design that is easy to recognize. The design of this recording machine uses a typing pattern of 10 fingers. Character input on the recording machine using multi touch 6 buttons used to form combinations in making braille. In this recording machine there is also a space function, enter and delete the last character. The process of making this recording machine will be done in several stages such as what is wanted, analysis, design, prototype and implementation / deploy. Based on the results of testing this recording machine can be concluded that in terms of usability involving blind respondents with status of students get an average scale of value 4 of (likert scale 1-5), so that the recorder machine is considered to meet the categories of learning ability, flexibility and robustness.